تحليل اداء سياسات سعر الصرف في تحقيق الاستقرار الاقتصادي في السودان - محمد احمدد. محمد عبد الله (Aljameai, 2026)
المستخلص : هدفت الورقة إلى دراسة تحليل اداء سياسات سعر الصرف في تحقيق الاستقرار الاقتصادي في السودان خلال الفترة 1992-2022، وإلى أي مدى تُعتبر هذه العوامل مُحددات لسعر الصرف في السودان. افترضت الورقة وجود علاقة ذات دلالة إحصائية بين الناتج المحلي الإجمالي والاحتياطي النقدي وحجم الصادرات والواردات وسعر الصرف. وتوصلت الورقة إلى أهم النتائج وهي أن هناك علاقة طردية موجبة بين سعر الصرف وكل من الناتج المحلي الإجمالي واحتياطي النقد الأجنبي وحجم الصادرات، وعلى العكس من ذلك، هناك علاقة عكسية سالبة بين سعر الصرف وحجم الواردات. وسجل معامل التحديد (R²) قيمة 0.96، أي أن 96٪ من إجمالي التغير في سعر الصرف الرسمي (OEX) يفسر بالمتغيرات المستقلة المتضمنة في نموذج سعر الصرف (الناتج المحلي الإجمالي، FR، M، X)، بينما يعزى 4٪ فقط إلى متغيرات أخرى غير متضمنة في النموذج والتي تساهم في الخطأ العشوائي. وأكدت إحصائية F البالغة 155.7328 (p < 0.01) دلالة النموذج. وكان معامل الارتباط بين المتغيرات المستقلة ضعيفًا، أقل من واحد، مما يدل على عدم وجود مشكلة ارتباط متعدد الخطوط. وقد تم استخدام اختبار ديكي فولر المُعزز (ADF) لتقييم ثبات بيانات السلاسل الزمنية، واختبار التكامل المشترك لجوهانسن للكشف عن العلاقات طويلة الأجل، وأشارت اختبارات السلاسل الزمنية إلى عدم استقرار في سعر الصرف نتيجةً للتقلبات الاقتصادية وعدم الاستقرار الناجم عن انفصال جنوب السودان عام 2011 وانخفاض التدفقات النقدية الخارجية من صادرات النفط. وقد ساهم ذلك في عجز الموازنة العامة للدولة، وعجز ميزان المدفوعات، وعدم استقرار سعر الصرف. وبناءً على هذه النتائج، أوصت الورقة بضرورة بناء وتنويع احتياطي النقد الأجنبي لزيادة فعالية سياسة سعر الصرف، من خلال زيادة الناتج المحلي الإجمالي الحقيقي، وخفض الواردات، وزيادة الصادرات. وعند صياغة سياسة سعر الصرف، يجب مراعاة تأثير الناتج المحلي الإجمالي على سعر الصرف، إذ يؤدي إلى استنزاف كبير للدخل من خلال الإنفاق على الواردات، مما قد يكون له تداعيات سلبية على سعر الصرف. Abstract: The paper aims to study the analysis performance of the exchange rate policies in achieving economic stability in Sudan during the period from 1992-2022, and to what extent these factors are considered determinants of the exchange rate in Sudan. The paper assumed that the Statistically significant between the gross domestic product, the monetary reserve, the volume of exports and imports, and the exchange rate.The paper reached the most important results, which are that There is a positive direct relationship between exchange rate and gross domestic product , foreign exchange reserve, export Volume, Conversely, there is a negative inverse relationship between the exchange rate and import volume.The coefficient of determination (R²) registered a value of 0.96, meaning that 96% of the total change in the official exchange rate (OEX) is explained by the independent variables included in the exchange rate model (GDP, FR, M, X), while only 4% is attributed to other variables not included in the model that contribute to random error.The F-statistic of 155.7328 (p < 0.01) confirmed the model’s significance. The correlation coefficient between the independent variables was weak, less than one, indicating the absence of a multicollinear correlation problem. with the Augmented Dickey-Fuller (ADF) test used to assess the stationarity of time series data and ,the Johansen cointegration test applied to detect long-term relationships. Time series tests indicated exchange rate instability resulting from economic fluctuations and the instability caused by the secession of South Sudan in 2011 and the decline in external cash flows from oil exports. This contributed to the state’s budget deficit, balance of payments deficit, and exchange rate instability. Based on these results, the paper recommended, It is essential to build and diversify foreign exchange reserve to increase the effectiveness of exchange rate policy, by increasing real GDP, reducing imports, and increasing exports. When formulating exchange rate policy, the impact of the GDP on Exchange rate must be considered, as it leads to a significant drain on income through import expenditure, which can have negative repercussions on the exchange rate.